NORMATIVE LEGAL ANALYSIS OF STOCK SPLIT REGULATION AS AN INSTRUMENT TO PREVENT PUMP AND DUMP PRACTICES IN INDONESIAN SHARIA CAPITAL MARKET - Nur Faizah; H.M Ridlwan Hambali; Anwar Saleh Hasibuan; Murnee Sueree (Universitas Muhammadiyah Prof DR HAMKA, 2026)
Research aims: This study aims to analyze the effectiveness of stock split regulation based on POJK Number 15 of 2022 and to assess market manipulation practices from the perspective of maqāṣid al-sharīʿah, especially ḥifẓ al-māl. Design/Methodology/Approach: This study employs a normative juridical method with an analytical approach, examining the stock split regulatory framework and evaluating its conformity with the principles of sharia economic law as stipulated in DSN-MUI Fatwa No. 40/2003 and No. 80/2011. Research findings: POJK No. 15/2022 is procedurally sufficient in establishing disclosure obligations, but it has not adequately addressed the speculative post-announcement market dynamics that leave retail investors vulnerable to manipulation driven by sentiment rather than fundamental analysis. From a sharia perspective, the exploitation of stock split momentum potentially contains elements of gharar and is contrary to the principle of justice (ʿadl). Theoretical Contribution/Originality: This study contributes an integrated analytical framework that combines capital market regulation with a maqāṣid-based Islamic legal approach to evaluate modern financial instruments. Practitioners/Policy Implications: The findings highlight the need for concrete coordination between the OJK, DSN-MUI, and the Indonesia Stock Exchange so that sharia principles can be effectively enforced rather than serving merely as ethical guidelines. Research Limitations/Implications: This study is limited to doctrinal normative analysis and does not involve empirical market data testing. Future research may validate these findings through quantitative or qualitative empirical approaches.